Umbral sentence example

umbral
  • As between the original and transformed quantic we have the umbral relations A1 = A1a1 d-A2a2, A2 = /21a1+/22a2, and for a second form B1 =A 1 b 1+ A 2 b 2, B 2 =/21bl +�2b2� The original forms are ax, bi, and we may regard them either as different forms or as equivalent representations of the same form.
    0
    0
  • This will be recognized as the resultant of the two linear forms. If the two linear forms be identical, the umbral sets a l, a2; b l, b 2 are alternative, are ultimately put equal to one another and (ab) vanishes.
    0
    0
  • As between the original and transformed quantic we have the umbral relations A1 = A1a1 d-A2a2, A2 = /21a1+/22a2, and for a second form B1 =A 1 b 1+ A 2 b 2, B 2 =/21bl +�2b2� The original forms are ax, bi, and we may regard them either as different forms or as equivalent representations of the same form.
    0
    0